Identification of Potential Biomarkers and Small Molecule Drugs for Cutaneous Melanoma Using Integrated Bioinformatic Analysis - Liu, Yong; Sun, Jiayi; Han, Dongran; Cui, Shengnan; Yan, Xiaoning (Frontiers in Cell and Developmental Biology, 2022)
Background: Cutaneous melanoma (CM) is a type of skin cancer with a high fatality rate, and its pathogenesis has not yet been fully elucidated. Methods: We obtained the gene expression datasets of MC through the Gene Expression Omnibus (GEO) database. Subsequently, robust rank aggregation (RRA) method was used to identify differentially expressed genes (DEGs) between CM cases and normal skin controls. Gene functional annotation was performed to explore the potential function of the DEGs. We built the PPI network by the Interactive Gene database retrieval tool (STRING) and selected hub modules by Molecular Complexity Detection (MCODE). We furthered and validated our results using the TCGA-GTEX dataset. Finally, potential small molecule drugs were predicted by CMap database and verified by molecular docking method. Results: Seven genes (GMPR, EMP3, SLC45A2, PDZD2, NPY1R, DLG5 and ADH1B) were screened out. Protein binding was the most significantly enriched in GO (gene ontology) analysis. KEGG pathway enrichment analysis showed that pathways in cancer and transcriptional misregulation in cancer were significantly enriched. Furazolidone was predicted and validated as a potential small-molecule drug for the treatment of CM, and we found that furazolidone may achieve its therapeutic purpose by acting on GMPR to inhibit CM cell proliferation rather than invasion. Conclusion: We identified 7 prognostic therapeutic targets associated with CM and furazolidone could be used as a potential drug for CM treatment, providing new prognostic markers, potential therapeutic targets and small molecule drugs for the treatment and prevention of CM.